The Impact of Global Financial Crisis on Capital Structure: Analyzing the Severity of Its Impact on Engineering SMEs in Pakistan? - Sarfaraz Ahmed Bhutto; Nazia Nazeer; Kewal Talreja (Metallurgical and Materials Engineering, 2025)
The current study examines the impact of global financial crises on the capital structure of engineering small and medium enterprises in Pakistan. The study takes GDP as an indicator of financial crises and total debt to total asset ratio, long-term debt to total debt ratio and long-term debt to total asset ratio as indicators of capital structure. The study mainly focuses on panel data from 5 years by including pre and post-crisis periods. The sample size of the study is 20 engineering small and medium enterprises in Pakistan. The research uses inferential statistical techniques to extract results. The findings depict that the financial crises have an insignificant effect on the capital structure of engineering small and medium enterprises in Pakistan. Moreover, by analyzing the statistics, we see that debt financing is frequently decreasing in engineering small and medium enterprises in Pakistan after the occurrence of this financial crisis globally.